Talk of the Town mobile app platform: New method for engaging family in STEM learning and research in homes and communities - Kominsky, Jonathan F.; Bascandziev, Igor; Shafto, Patrick; Bonawitz, Elizabeth (Frontiers in Psychology, 2023)
Children do not just learn in the classroom. They engage in “informal learning” every day just by spending time with their family and peers. However, while researchers know this occurs, less is known about the science of this learning—how this learning works. This is so because investigators lack access to those moments of informal learning. In this mini-review we present a technical solution: a mobile-based research platform called “Talk of the Town” that will provide a window into children’s informal learning. The tool will be open to all researchers and educators and is flexibly adaptable to these needs. It allows access to data that have never been studied before, providing a means for developing and testing vast educational interventions, and providing access to much more diverse samples than are typically studied in laboratories, homes, and science museums. The review details the promise and challenges associated with these new methods of data collection and family engagement in STEM learning sciences.